A Novel Concept for the Removal of Solvent Vapors from Exhaust Air - Ludgen, Diana; Wichmann, Hubertus; Bahadir, Muefit (Clean : soil, air, water, 2013)
The emission of large amounts of solvent vapors with exhaust air from industrial production into the environment is a serious problem. In Germany, industry‐sector‐specific threshold values are applied and technical measures for pollution reduction are required. Different techniques for exhaust air cleaning are in use but still posing problems concerning costs and reliability. For these reasons, the development of processes for exhaust air treatment is the subject of the current research. A new concept for exhaust air cleaning is introduced that combines absorption of a solvent vapor by an organic fluid and a subsequent adsorption by a molecular sieve placed in the absorber. It was managed to close the loops of solvent recovery and sorbents regeneration. In laboratory‐scale experiments it was possible to reduce an initial ethylacetate pollution of 800 mg/m3 or 349 mg C/m3 below the limit value of 75 mg C/m3 over 60 h duration. Thermogravimetric measurements assisted to define optimum conditions for solvent recovery at 180°C from the molecular sieve. One unexpected positive finding was the considerable increase in the solvent release in the presence of the absorption fluid while adsorption isotherms revealed first insight into this process. A combined absorption and adsorption procedure for exhaust air purification from VOC was developed. It could be successfully applied at laboratory‐scale. The recovery and regeneration loops of the exhaust air purification concept could be closed.